2021
DOI: 10.3389/fonc.2021.766851
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-P15-041, A Novel Bone Imaging Agent for Diagnosis of Bone Metastases

Abstract: Objectives68Ga-P15-041 (68Ga-HBED-CC-BP) is a novel bone-seeking PET radiotracer, which can be readily prepared by using a simple kit formulation and an in-house 68Ga/68Ge generator. The aim of this study is to assess the potential human application of 68Ga-P15-041 for clinical PET/CT imaging and to compare its efficacy to detect bone metastases of different cancers with 99mTc-MDP whole-body bone scintigraphy (WBBS).MethodsInitial kinetic study using Patlak analysis and parametric maps were performed in five h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This agent was an extension of previously reported [ 68 Ga]­Ga-HBED-CC-bisphosphonate ([ 68 Ga]­Ga-P15-041), successfully applied in detecting bone lesions associated with tumor metastasis in cancer patients. , We aim to extend the application of this ligand to the treatment of bone metastases by labeling it with therapeutic radionuclides, such as lutetium-177, actinium-225, and others. Although it was reported that Lu­(III) forms a complex with HBED with high stability constant (logKd = 20.4), no further [ 177 Lu]­Lu-HBED-CC-related complexes are mentioned in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agent was an extension of previously reported [ 68 Ga]­Ga-HBED-CC-bisphosphonate ([ 68 Ga]­Ga-P15-041), successfully applied in detecting bone lesions associated with tumor metastasis in cancer patients. , We aim to extend the application of this ligand to the treatment of bone metastases by labeling it with therapeutic radionuclides, such as lutetium-177, actinium-225, and others. Although it was reported that Lu­(III) forms a complex with HBED with high stability constant (logKd = 20.4), no further [ 177 Lu]­Lu-HBED-CC-related complexes are mentioned in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a bone imaging agent, ([ 68 Ga]­Ga-HBED-CC-bisphosphonate, [ 68 Ga]­Ga-P15-041), containing HBED-CC and bisphosphonate groups was prepared (Figure ) and it showed excellent bone uptake and efficient detection of bone metastasis in cancer patients. , By adding an additional DOTA chelator, P15-041 was converted to P15-073, 1 , which can accommodate different α- or β – -emitting metals, i.e., lutetium­(III)-177, actinium­(III)-225, and other metal-based radionuclides, for the formation of stable complexes as bone-seeking drugs (Figure ). The desired DOTA-HBED-CC-bisphosphonate (P15-073, 1 ) contains two chelators: DOTA and HBED-CC.…”
Section: Introductionmentioning
confidence: 99%
“…As smaller, intact, functional antigen binding agents with a small size (12–15 kDA), nanobodies demonstrate strong tissue penetration and high affinity and stability, revealing treatment pharmacokinetics and pharmacodynamics compatible with short-lived radioisotopes. They are more suitable for tracking advanced tumors [ 81 , 82 , 83 ].…”
Section: Nanobody Applications In Medical Researchmentioning
confidence: 99%
“…39−41 A bisphosphonate ([ 68 Ga]Ga-P15-041) has been tested in humans for imaging bone metastasis. 25,26,42 Using DOTA derivatives as the chelator and the same PSMA binding moiety and linker (Glu-NH-CO-NH-Lys-Phe-O-carboxymethyl)-Tyr-= X in blue) from the diagnostic agent, [ 68 Ga]Ga-P16-093, [ 177 [ 177 Lu]Lu-1 displayed superior dual-targeting properties and therefore may be a promising new therapeutic agent for prostate cancer, targeting both PSMA tumors and bone metastases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A PSMA-targeting imaging agent, [ 68 Ga]­Ga-P16–093, was successfully prepared , and tested in humans. A bisphosphonate ([ 68 Ga]­Ga-P15-041) has been tested in humans for imaging bone metastasis. ,, Using DOTA derivatives as the chelator and the same PSMA binding moiety and linker (Glu-NH-CO-NH-Lys-Phe- O -carboxymethyl)-Tyr- = X in blue) from the diagnostic agent, [ 68 Ga]­Ga-P16-093, [ 177 Lu]­Lu-P19-065 (Approach #1) and [ 177 Lu]­Lu-P17–087, [ 177 Lu]­Lu-P17-088 (Approach #2) were successfully transformed to radionuclide therapy agents. To develop hetero-bivalent agents, R = Gly-bisphosphonate was added for targeting bone metastasis, resulting in the formation of hetero-bivalent agents, [M]-P17-079 ([M]-1) and [M]-P17-081 ([M]-2) with [M] = [ 68 Ga/ 177 Lu].…”
Section: Introductionmentioning
confidence: 99%